Novel Cyclic Lipopeptides Fusaricidin Analogs for Treating Wound Infections - Gil, Joel; Pastar, Irena; Houghten, Richard A.; Padhee, Shruti; Higa, Alexander; Solis, Michael; Valdez, Jose; Head, Cheyanne R.; Michaels, Heather; Lenhart, Brian; Simms, Colin; Williams, Brandon; et al. (Frontiers in Microbiology, 2021)
Both acute and chronic cutaneous wounds are often difficult to treat due to the high-risk for bacterial contamination. Once hospitalized, open wounds are at a high-risk for developing hospital-associated infections caused by multi drug-resistant bacteria such as Staphylococcus aureus and Pseudomonas aeruginosa. Treating these infections is challenging, not only because of antibiotic resistance, but also due to the production of biofilms. New treatment strategies are needed that will help in both stimulating the wound healing process, as well as preventing and eliminating bacterial wound infections. Fusaricidins are naturally occurring cyclic lipopeptides with antimicrobial properties that have shown to be effective against a variety of fungi and gram-positive bacteria, with low toxicity. Continuing with our efforts toward the identification of novel cyclic lipopeptides Fusaricidin analogs, herein we report the synthesis and test results of the antimicrobial activity for two novel cyclic lipopeptides (CLP), CLP 2605-4 and CLP 2612-8.1 against methicillin resistant S. aureus and P. aeruginosa, respectively, in in vivo porcine full thickness wound model. Both CLPs were able to reduce bacterial counts by approximately 3 log CFU/g by the last assessment day. Peptide 2612-8.1 slightly enhanced the wound healing, however, wounds treated with peptide 2605-4, have shown higher levels of inflammation and impaired wound healing process. This study highlights the importance of identifying new antimicrobials that can combat bacterial infection while not impeding tissue repair